2012
DOI: 10.1186/cc11467
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is the strongest predictor of 30-day mortality in patients with cardiogenic shock due to myocardial infarction

Abstract: IntroductionCardiogenic shock (CS) remains the leading cause of death in patients hospitalized for myocardial infarction (MI). Systemic inflammation with inappropriate vasodilatation is observed in many patients with CS and may contribute to an excess mortality rate. The purpose of this study was to determine the predictive role of serial measurements of Nt-proBNP, interleukin-6 (IL-6), and procalcitonin (PCT) for 30-day mortality in patients with CS due to MI.MethodsThe present study is a prospective single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…Despite promising early results [15], subsequent randomized controlled studies failed to demonstrate a mortality benefit [16,17]. A number of cytokines are involved in the cascade of inflammation that accompanies severe cardiogenic shock, and it is likely that there are shared characteristics between cardiogenic and septic shock [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising early results [15], subsequent randomized controlled studies failed to demonstrate a mortality benefit [16,17]. A number of cytokines are involved in the cascade of inflammation that accompanies severe cardiogenic shock, and it is likely that there are shared characteristics between cardiogenic and septic shock [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that treatment with anti-IL-6 antibody lowered hepcidin levels which alleviated hypoferremia and restored iron homeostasis [ 2 , 69 ]. Among many inflammatory mediators IL-6 is a predictor of mortality in chronic kidney disease [ 70 ], in HIV [ 71 ], and in other chronic diseases associated with immune activation due to microbial translocation [ 72 , 73 ]. Our results suggest that ER stress combined with inflammation increases IL-6 that induces hepcidin expression leading to increased intracellular iron which downregulates BDH2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works on acute‐on‐chronic liver failure have shown high cytokine levels . The prognostic value of IL‐6 levels has already been demonstrated in other acute situations such as ICU patients after cardiac and septic shock as well as in trauma patients . SIRS and sepsis may explain higher IL‐6 levels both in the pre‐ and immediate posttransplant setting.…”
Section: Discussionmentioning
confidence: 99%